Factors affecting the community’s attitude toward COVID-19 vaccination: cross-sectional study - Chintia Gracelia Amalo; Ezra Amarya Ekaristy; Maretty Wattileo; Martina Pakpahan; Ester Silitonga (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objective: The study aimed to analyze the factors that affect the community’s attitude towards COVID-19 vaccination in Tangerang District. Methods: A cross-sectional study was used. Convenience sampling was used to select 400 respondents. Inclusion criteria are living in Tangerang District, aged between 18 and 55, and earning a living. An online questionnaire was used and passed validity and reliability tests. This study received ethical approval. Results: Most respondents had a high level of education (48.50%), low income (72.50%), high knowledge (78%), and a positive attitude (76.50%) regarding vaccination against COVID-19. The Chi-square test revealed a correlation between knowledge and attitudes towards COVID-19 vaccination (p=0.001), as well as education levels (p=0.001), but there was no correlation between income and attitudes (p=0.094). Conclusions: Health professionals should engage in extensive socialization and face-to-face visits with people with limited access to information to promote a positive attitude and expand the scope of COVID-19 vaccination.